Pengajaran Bahasa Inggris Terhadap Siswa Sekolah Dasar dengan Menggunakan Video Animasi - Mike Nurmalia Sari; Pretty Elisa Ayu Ningsih (Jurnal Abdimas Adpi Sosial dan Humaniora, 2023)
This Community Service activity is carried out at Elementary School level students grades 3-5. The activity was carried out in Four Belui Villages, Depati VII District, Kerinci Regency, Jambi Province. This activity aims to provide learning English materials to students at the elementary school level by utilizing Video Animation media. To see the effect of teaching English using animated videos on students' abilities, a pretest and post-test were carried out. The results of the activity showed a significant increase in the ability of students who were given activities with an increase in student scores before teaching using animated videos and after teaching was carried out. In terms of student motivation also seems to increase. This is indicated by the enthusiasm shown by the students during the activity.